Negative electrode and preparation method thereof, secondary battery and electric equipment
By using lithium supplement agent in the silicon-based anode of solid state batteries to react with silicon-based anode particles to form lithium silicon alloy, the problems of irreversible consumption of lithium ions and flammable and explosive lithium metal are solved, the first cycle efficiency and circulation performance of the battery are improved, and the safety risks are reduced.
Patent Information
- Application Number
- CN202311269833.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silicon-based negative electrode of solid-state batteries is prone to side reactions with lithium ions during the first charging cycle, resulting in irreversible consumption of lithium ions, reducing the battery's first circulation efficiency, and posing a safety hazard of flammable, explosive lithium metal and large-area enrichment.
A negative electrode preparation method is adopted to provide a negative electrode precursor containing silicon-based negative electrode material particles and lithium supplement agent, so that the lithium supplement agent is delimited and reacted with the silicon-based negative electrode material particles to form a lithium silicon alloy, avoiding the direct use of lithium metal and reducing production safety risks.
While achieving lithium supplementation for negative electrodes, it improves the first cycle efficiency and circulation performance of the battery, reduces the safety risks of production and storage, and is suitable for large-scale industrial production.
Smart Images

Figure BDA0004475306920000151 
Figure BDA0004475306920000161
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] Solid-state batteries have attracted widespread attention due to their light weight and high energy density. At present, solid-state batteries often use silicon-based negative electrodes, which are prone to side reactions with lithium ions during the first charging cycle of the battery, resulting in irreversible consumption of lithium ions, which in turn reduces the first cycle efficiency of the battery.
[0003] To solve the above problems, the industry often chooses to pre-lithiate the negative electrode to improve the first cycle efficiency of the battery. The industry generally adopts the method of directly mixing lithium metal strips or lithium metal powders into the negative electrode or pressing them on the surface of the negative electrode active material layer to achieve this. However, this not only has strict requirements on process conditions, but also has safety issues such as flammability and explosion during processing. In addition, lithium metal will spontaneously react with silicon-based negative electrode active materials to produce lithium silicon alloys. Therefore, the above preparation method will also cause the negative electrode before assembly into the battery to have a large area of enriched lithium silicon alloys directly exposed to the air. The large area of enriched lithium silicon alloys has poor stability in the air and is flammable, which will cause the above negative electrode to have a large safety hazard during storage and battery assembly. Summary of the invention
[0004] In view of this, the present application provides a negative electrode and a preparation method thereof, a secondary battery and an electrical device. During the preparation process of the negative electrode, there is no problem of flammability and explosion of lithium metal, and the risk of large-area enriched lithium-silicon alloy being directly exposed to the air can be fully reduced. Therefore, the preparation method can achieve negative electrode lithium replenishment while greatly reducing production safety hazards; and the secondary battery with the negative electrode has both high first cycle efficiency and good cycle performance.
[0005] The first aspect of the present application provides a method for preparing a negative electrode, comprising:
[0006] Providing a negative electrode precursor, wherein the negative electrode precursor comprises silicon-based negative electrode material particles and a lithium supplement agent;
[0007] The lithium supplement agent is de-lithiated, and the de-lithiated lithium ions react with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy;
[0008] The lithium supplement includes at least one of Li3P, Li3B, lithium polysulfide ranate, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, crotonate lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cuphexaquinone lithium, tris(4-nitrosophenyl)amine lithium, cyclohexanehexaone lithium and dipentamethylenethiuram hexasulfide lithium.
[0009] The above preparation method is simple and easy to implement, with strong process reliability, and realizes one-step lithium replenishment, which simplifies the lithium replenishment process; moreover, the above preparation method does not require the introduction of lithium metal to form lithium-silicon alloy, has relatively loose requirements on the preparation environment, has high production efficiency, greatly improves the safety of the negative electrode during the preparation process, and can realize large-scale industrial production. Furthermore, the secondary battery prepared by the above preparation method has a high first cycle efficiency and excellent cycle performance.
[0010] Optionally, the lithium supplement surface capacity of the negative electrode precursor is 0.3 mAh / cm 2 -3.0mAh / cm 2 .
[0011] Optionally, the material of the silicon-based negative electrode material particles includes at least one of silicon, silicon oxide and silicon-carbon composite;
[0012] Preferably, the carbon content of the silicon-carbon composite is less than or equal to 5 wt.%;
[0013] Preferably, the oxygen content of the silicon oxide is less than or equal to 18 wt.%.
[0014] Optionally, the method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain the negative electrode comprising a lithium-silicon alloy comprises heating the negative electrode precursor.
[0015] Optionally, the heat treatment comprises: drying the negative electrode precursor at 100° C. to 150° C. for 20 min to 40 min, and then baking at 100° C. to 170° C. for 30 min to 720 min.
[0016] Optionally, the method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy includes assembling the negative electrode precursor into a battery cell and chemically forming the battery cell.
[0017] Optionally, the negative electrode precursor further includes a current collector, and the method for providing the negative electrode precursor includes mixing the silicon-based negative electrode material particles and the lithium supplement agent to obtain a mixture, and disposing the mixture on the surface of the current collector.
[0018] Optionally, the mixture includes the silicon-based negative electrode material particles, solid electrolyte, conductive agent and binder in a mass ratio of (60-99): (0-35): (0-5): (1-5). The second aspect of the present application provides a negative electrode, including at least one of inorganic phosphide, inorganic boride, polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonic acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexane hexaketone and hexasulfide dipentamethylenethiuram at least one, and lithium silicon alloy.
[0019] The secondary battery with the above negative electrode can achieve higher first cycle efficiency and cycle performance.
[0020] Optionally, the negative electrode further includes silicon-based negative electrode material particles.
[0021] Optionally, the lithium silicon alloy is in granular form, and a D50 particle size of the lithium silicon alloy is less than or equal to 3 μm; preferably, a D50 particle size of the lithium silicon alloy is in the range of 1 μm to 2 μm.
[0022] Optionally, the negative electrode includes at least one of polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris(4-nitrosophenyl)amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide.
[0023] Optionally, at least one of the lithium silicon alloy and the inorganic phosphide, inorganic boride, polysulfide, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonic acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide is Li3P, L At least one of i3B, lithium polysulfide ranate, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, crotonate lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cup hexaquinone lithium, tris(4-nitrosophenyl)amine lithium, cyclohexanehexaone lithium and dipentamethylenethiuram hexasulfide lithium is reacted in situ with silicon-based negative electrode material particles to generate.
[0024] Optionally, the negative electrode further comprises a solid electrolyte. Optionally, the solid electrolyte comprises a sulfide solid electrolyte.
[0025] The third aspect of the present application provides a secondary battery, comprising the negative electrode provided in the first aspect of the present application, or the negative electrode prepared by the preparation method provided in the second aspect of the present application. Due to the presence of the negative electrode provided in the embodiment of the present application, the secondary battery has both high first cycle efficiency and good cycle performance.
[0026] Optionally, the secondary battery further comprises a positive electrode and a solid electrolyte disposed between the negative electrode and the positive electrode. Further, the solid electrolyte comprises a sulfide solid electrolyte.
[0027] The fourth aspect of the present application provides an electric device, comprising the secondary battery provided by the third aspect of the present application. Due to the secondary battery provided by the embodiment of the present application, the electric device has strong market competitiveness.
[0028] Optionally, the electrical equipment includes consumer electronic products, vehicles, etc. DETAILED DESCRIPTION
[0029] Silicon-based negative electrode materials (e.g., silicon, silicon oxide, etc.) have a high theoretical specific capacity and are often used as negative electrode materials for solid-state batteries. However, the surface of silicon-based negative electrode material particles or the material itself carries O atoms, C atoms, etc., which react with active lithium ions to generate substances such as Li4SiO4, resulting in irreversible consumption of active lithium ions, and thus resulting in a low first cycle efficiency of the battery. The industry often uses negative electrode lithium supplementation to improve the first cycle efficiency of solid-state batteries. The industry generally achieves negative electrode lithium supplementation by directly mixing lithium metal strips or lithium metal powders into the negative electrode or pressing them on the surface of the negative electrode active material layer. However, this not only has strict requirements on process conditions, but also has safety issues such as flammability and explosion during processing. Moreover, lithium metal will spontaneously react with silicon-based negative electrode active materials to produce lithium silicon alloys. Therefore, the above preparation method will also lead to large-scale enrichment of lithium silicon alloys in the negative electrode, and the large-area enriched lithium silicon alloys have poor stability and are flammable in the air, resulting in the above negative electrode also having a large safety hazard during storage and battery assembly.
[0030] There are also literature reports that a lithium metal layer is separately set in the silicon-based negative electrode to supplement lithium, and the lithium metal layer is set between two stacked silicon-based negative electrode active material layers, in an attempt to reduce the risk of lithium metal reacting with air. However, if you want to obtain a negative electrode with the above structure, you must first set the first negative electrode active material layer, the lithium metal layer and the second negative electrode active material layer in sequence on the surface of the negative electrode current collector. Because the lithium metal layer will react violently with substances such as water, the second active material layer can only be prepared by a dry method. The current dry preparation technology makes it difficult to achieve a flatness of the active material layer within 1μm, and the low flatness of the active material layer will cause uneven shrinkage of the active material layer during the battery charge and discharge cycle, which can easily lead to battery failure. In addition, there is still a problem of large-area enrichment of lithium metal in the above-mentioned negative electrode, so there is still a large safety risk.
[0031] To solve the above problems, the present invention provides a method for preparing a negative electrode, comprising the following steps:
[0032] Providing a negative electrode precursor, wherein the negative electrode precursor comprises silicon-based negative electrode material particles and a lithium supplement agent;
[0033] The lithium supplement agent is de-lithiated, and the de-lithiated lithium ions react with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy. It can be understood that in some embodiments, the lithium-silicon alloy in the negative electrode is in a granular form.
[0034] The lithium supplement includes at least one of Li3P, Li3B, lithium polysulfide ranate, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, crotonate lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cuphexaquinone lithium, tris(4-nitrosophenyl)amine lithium, cyclohexanehexaone lithium and dipentamethylenethiuram hexasulfide lithium.
[0035] In the embodiments of the present application, for the convenience of description, Li3P and Li3B are referred to as "inorganic lithium supplements" in the specification, and the lithium supplements other than Li3P and Li3B are collectively referred to as "organic lithium supplements".
[0036] There is a potential difference between the lithium supplement agent and the silicon-based negative electrode material particles (for example, Li3P and Li3B, etc.), and / or, the functional groups on the surface of the lithium supplement agent (for example, lithiated carboxylic acid groups, carbonyl groups, ester groups, amino groups, thiol groups, sulfonic acid groups, formyl groups, acetyl groups, etc.) undergo redox reactions, which lowers its chemical barrier, thereby forming a chemical potential difference with the silicon-based negative electrode material particles, so that the silicon atoms in the silicon-based negative electrode material particles can react with lithium ions to form an alloy, thereby generating a lithium-silicon alloy in situ in the silicon-based negative electrode material particles, and the product after the lithium supplement agent is de-lithiated is dispersed in the negative electrode; therefore, even if a reaction occurs between the lithium supplement agent and the silicon-based negative electrode material particles, no vacancies will be caused in the negative electrode, and the resulting negative electrode structure is stable. Moreover, the lithium-silicon alloy is generated by the reaction of the lithium supplement agent and the silicon-based negative electrode material particles, which can avoid the flammable and explosive problems caused by the lithium metal raw materials in the prior art, and the lithium supplement agent will form a lithium-depleted product after lithium is removed. The lithium-depleted product is dispersed between the formed lithium-silicon alloy, reducing the risk of lithium-silicon alloy enrichment. In addition, the released lithium ions react with substances on the surface of the silicon-based negative electrode material particles, and / or the lithium ions enter the interior of the silicon-based negative electrode material particles and react with silicon atoms to form a lithium-silicon alloy. Therefore, the lithium-silicon alloy just obtained is essentially divided into lithium-rich regions and silicon-rich regions, which can also further reduce the risk of large-area enrichment of lithium-silicon alloy and exposure to the air.
[0037] The above preparation method is simple and easy, with strong process reliability, and realizes one-step lithium replenishment, simplifying the lithium replenishment process. Moreover, the above preparation method does not require the introduction of lithium metal to form a lithium-silicon alloy, has relatively loose requirements on the preparation environment, has high production efficiency, greatly improves the safety of the negative electrode during the preparation process, and can realize large-scale industrial production.
[0038] In some embodiments of the present application, the method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy includes heating the negative electrode precursor. In this way, the formation of a silicon-lithium alloy can be promoted. In some specific embodiments, during the above heating process, part of the lithium in the lithium supplement agent is removed to form a lithium-silicon alloy, so at this time, there is no large-area lithium-silicon accumulation in the negative electrode.
[0039] In some embodiments of the present application, the above-mentioned heating treatment includes: drying the negative electrode precursor at 100°C to 150°C for 20min to 40min, and then baking at 100°C to 170°C for 30min to 720min. In some specific embodiments, the above-mentioned negative electrode precursor is vacuum-baked at 105°C to 135°C for 6h to 12h. In particular, during the above-mentioned baking process, at the above-mentioned temperature, the in-situ reaction efficiency of the lithium supplement agent and the silicon-based negative electrode material particles is high, which is conducive to improving production efficiency. Exemplarily, the above-mentioned drying temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 145°C, etc., and the drying time can be 20min, 25min, 30min, 35min, etc. Exemplarily, the above-mentioned baking temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 145°C, 150°C, 160°C, 165°C, etc. Exemplarily, the baking time can be 30 min, 35 min, 40 min, 50 min, 60 min, 100 min, 150 min, 200 min, 250 min, 300 min, 350 min, 400 min, 450 min, 500 min, 550 min, 600 min, 650 min, 700 min, etc.
[0040] In some embodiments of the present application, the method of making the lithium supplement agent delithiate, and the lithium ions released react with the silicon-based negative electrode material particles to obtain a negative electrode containing a lithium-silicon alloy includes assembling the negative electrode precursor into a battery cell and forming the battery cell. In this way, the release of lithium ions in the lithium supplement agent and the generation of lithium-silicon alloy can be fully promoted. It can be understood that even if a large amount of lithium-silicon alloy is generated in the above process, it is also generated in the closed environment of the battery cell. Even if there is a large area of lithium-silicon alloy enrichment at this time, there is no problem of direct exposure to the air. It can be understood that for silicon-based negative electrode materials, the active sites (for example, O atoms, C atoms, etc.) on its surface or in itself, during the first cycle of the battery, the silicon-based negative electrode material will capture the active lithium ions released from the positive electrode and react with the above-mentioned active sites, resulting in irreversible loss of active lithium ions, causing the first efficiency of the battery to decrease and affecting the cycle performance of the battery. During the above-mentioned formation process, the lithium released by the lithium supplement can replace the active lithium ions released from the positive electrode and be captured by the silicon-based negative electrode material particles, thereby improving the first cycle efficiency and cycle performance of the battery cell (i.e., battery). It can be understood that the battery cell also includes a positive electrode and a solid electrolyte layer located between the positive electrode and the negative electrode. The above-mentioned positive electrode and solid electrolyte layer can be selected from any known positive electrode and solid electrolyte layer in the art. Specifically, the material of the above-mentioned solid electrolyte layer is preferably a sulfide solid electrolyte.
[0041] It can be understood that in some specific embodiments, the method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy includes firstly heating the negative electrode precursor, then assembling the heated negative electrode precursor into a battery cell, and forming the battery cell. After the negative electrode precursor is cooled, the negative electrode precursor is assembled into a battery cell.
[0042] In some embodiments of the present application, the lithium supplement surface capacity of the negative electrode precursor is 0.3 mAh / cm 2 -3.0mAh / cm 2 In some embodiments of the present application, the lithium replenishment surface capacity of the negative electrode is 0.3 mAh / cm 2 -3.0mAh / cm 2 In the present application, the lithium replenishment surface capacity of the negative electrode precursor refers to the irreversible capacity of the negative electrode precursor before the first charge and discharge cycle. For example, the lithium replenishment surface capacity of the negative electrode precursor can be 0.30 mAh / cm 2 , 0.32mAh / cm 2 、0.35mAh / cm 2 、0.40mAh / cm 2 、0.45mAh / cm 2 、0.50mAh / cm 2 、0.80mAh / cm 2 、0.90mAh / cm 2 、1.00mAh / cm 2 、1.20mAh / cm 2 、1.50mAh / cm 2 、1.80mAh / cm 2 、2.00mAh / cm 2 , 2.20mAh / cm 2 、2.50mAh / cm 2 、2.80mAh / cm 2 、2.90mAh / cm 2 In the embodiment of the present application, the lithium replenishment surface capacity of the negative electrode precursor is: when the negative electrode precursor and the positive electrode are assembled into a battery, and the battery is charged and discharged at a rate of 0.1C, the lithium replenishment surface capacity of the negative electrode precursor = (the initial charging capacity of the battery - the initial discharge capacity of the battery) / the total area of the negative electrode active material layer. The unit of the lithium replenishment surface capacity of the negative electrode precursor is mAh / cm 2. Among them, the above-mentioned positive electrode includes a positive electrode current collector and a positive electrode material layer, and the positive electrode material layer is composed of a NCM811 positive electrode coated with Li3BO3 with a mass ratio of 85:13:1.5:0.5, a Li6PS5Cl solid electrolyte, a Super P conductive agent, and polytetrafluoroethylene. Controlling the lithium replenishment surface capacity of the negative electrode precursor within the above range can not only contribute a sufficient amount of active lithium ions during the battery cycle to make up for the irreversible consumption of active lithium ions and improve the first cycle efficiency of the battery; at the same time, it will not affect the reversible capacity of the final negative electrode, thereby helping to ensure that the battery has a high energy density. In addition, it can be understood that the lithium replenishment surface capacity of the negative electrode precursor mainly depends on the amount of lithium replenisher added during the preparation of the negative electrode precursor. Controlling the lithium replenishment surface capacity of the negative electrode precursor within a suitable range is also controlling the amount of lithium replenisher added within a suitable range, so as to effectively reduce the risk of local lithium precipitation during the battery formation process, thereby ensuring that the battery has good cycle performance. In some embodiments, the lithium ions released by the lithium replenisher react with part of the silicon-based negative electrode material particles to form a lithium-silicon alloy. Therefore, at this time, the prepared negative electrode includes lithium-silicon alloy, silicon-based negative electrode material particles and the product after the lithium supplement agent is de-lithiated.
[0043] In some embodiments of the present application, the negative electrode precursor further includes a current collector, and the method for providing the negative electrode precursor includes mixing the silicon-based negative electrode material particles and the lithium supplement agent to obtain a mixture, and placing the mixture on the surface of the current collector. In this way, the silicon-based negative electrode particles and the lithium supplement agent can be fully contacted, thereby facilitating the full reaction between the two to generate a silicon-lithium alloy.
[0044] In some embodiments of the present application, silicon-based negative electrode material particles and lithium supplement agents are dispersed in a solvent and mixed to obtain negative electrode slurry (that is, the mixture is negative electrode slurry). In this way, silicon-based negative electrode material particles and lithium supplement agents can be fully contacted during the preparation of negative electrode slurry, and the lithium supplement agent will not have side reactions with other substances in the slurry (for example, solvent), and a negative electrode slurry with high uniformity and good stability can be obtained.
[0045] In some embodiments of the present application, silicon-based negative electrode material particles include but are not limited to elemental silicon, silicon oxide (SiOx), and silicon-carbon composites. Among them, silicon-carbon composites include but are not limited to a mixture of silicon particles and carbon materials, and silicon particles coated with a carbon layer (silicon as the core).
[0046] In some embodiments of the present application, the silicon-based negative electrode material particles are selected from silicon single substance particles. At this time, the above-mentioned negative electrode will change during the cycle of the battery, and the granular lithium-silicon alloy will gradually fuse into a block-like substance. Specifically, during the formation / charge and discharge cycle of the solid-state battery system, the silicon single substance expands after being amorphized by lithium insertion, and can undergo welding-fusion with other silicon single substance particles to become a block composed of amorphous materials. The block has sufficient electronic conductivity and ionic conductivity, and the structure has considerable stability, so it can circulate relatively stably in the solid-state battery system. In addition, silicon single substance is stable to the electrolyte, and the first efficiency of the battery can be as high as 82-85%.
[0047] In some specific embodiments of the present application, the mass percentage of carbon is less than or equal to 5.0% based on the total mass of the silicon-carbon composite. For example, the mass percentage of carbon can be, but is not limited to, 0.1%, 0.5%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, etc. Further, in some specific embodiments, the thickness of the carbon layer on the surface of the silicon core is in the range of 3nm to 10nm. For example, the thickness of the above-mentioned carbon layer can be, but is not limited to, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc. In this way, it is beneficial for lithium ions to pass through the carbon layer and react with the silicon core to form a lithium-silicon alloy.
[0048] In some specific embodiments of the present application, the oxygen content is less than or equal to 18% based on the total mass of SiOx. In this way, the influence of oxygen on the first effect will be reduced to an acceptable range, the required amount of lithium supplementation will be reduced, and the production cost of the pole piece and the battery will be reduced.
[0049] In some embodiments of the present application, the D50 particle size of the silicon-based negative electrode material particles is less than or equal to 3μm. In some specific embodiments, the D50 particle size of the silicon-based negative electrode material particles is in the range of 0.2μm to 2μm. In this way, the silicon-based negative electrode material particles have a more suitable specific surface area, which is conducive to the reaction of lithium ions released from the lithium supplement agent with it / facilitating the diffusion of lithium ions released from the lithium supplement agent to the silicon-based negative electrode material particles, thereby facilitating the rapid formation of lithium-silicon alloys. In addition, because the above-mentioned D50 particle size is a genetic structure, controlling the D50 particle size of the silicon-based negative electrode material particles within the above-mentioned range is also conducive to the extraction / embedding of active lithium ions during the battery cycle, and thus to the rate performance of the battery. In some embodiments of the present application, the BET specific surface area of the silicon-based negative electrode material particles is 1.0m 2 / g~2.2m 2 For example, the BET specific surface area of the silicon-based negative electrode material particles may be 1.0 m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.15m 2 / g, etc. In this way, it is beneficial to react with the inorganic lithium supplement during the heating process, and it is also beneficial for the lithium ions released by the organic lithium supplement to diffuse into the silicon-based negative electrode material particles, thereby facilitating the formation of lithium-silicon alloy; at the same time, it is also beneficial for the deintercalation of lithium ions during the subsequent battery charge and discharge cycle.
[0050] In some embodiments of the present application, a binder and an optional solid electrolyte and an optional conductive agent are also added to the mixture. For the convenience of description, the mixture of silicon-based negative electrode material particles, binders, possible solid electrolytes, and possible conductive agents is referred to as "first raw materials". In some specific embodiments, the first raw material includes the following components in parts by weight: 60 to 99 parts of the silicon-based negative electrode material particles, 0 to 35 parts of solid electrolytes, 0 to 5 conductive agents, and 1 to 5 parts of binders. Exemplarily, the weight parts of silicon-based negative electrode material particles can be 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts, 98 parts, etc. Exemplarily, the weight parts of solid electrolytes can be 1 part, 2 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, etc. Exemplarily, the weight percentage of the conductive agent can be 0, 1, 2, 3, 4, 5, etc. Exemplarily, the weight percentage of the binder can be 0, 1, 2, 3, 4, 5, etc. In other words, the aforementioned mixture includes the silicon-based negative electrode material particles, the solid electrolyte, the conductive agent and the binder in a mass ratio of (60-99): (0-35): (0-5): (1-5).
[0051] In some embodiments of the present application, silicon-based negative electrode material particles, solid electrolyte, conductive agent and binder may be fully mixed to obtain a first raw material, and then the first raw material is mixed with a lithium supplement to obtain the aforementioned mixture.
[0052] In some specific embodiments of the present application, the first raw material, that is, silicon-based negative electrode material particles, solid electrolyte, conductive agent and binder can be mixed by a high-speed disperser to obtain the first raw material. In some specific embodiments, the speed of the high-speed disperser is 500rpm to 2000rpm, and the mixing time is 10min to 120min, preferably 20min to 60min. Then, a small amount of solvent is added to the above-mentioned first raw material and kneaded, and the kneading time is 30min to 120min. After the kneading is completed, the solvent is continued to be added to the obtained material so that the solid content of the slurry reaches 40% to 60%, and the lithium supplement agent is added at the same time, and stirred under vacuum for 10min to 60min to obtain the negative electrode slurry (that is, the aforementioned mixture), and the viscosity of the negative electrode slurry reaches 1800Pa / s to 3200Pa / s.
[0053] In some embodiments of the present application, based on the total mass of the first raw material, the mass percentage of the silicon-based negative electrode material particles is 90% to 99%. For example, the mass percentage of the silicon-based negative electrode material particles in the first raw material can be, but is not limited to, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc.
[0054] In some embodiments of the present application, the solid electrolyte includes but is not limited to Li6PS5Cl, Li 10 GeP2S 12 , Li 10 Ge 0.5 Si 0.5 P2S 12 、Li7P3S 11 At least one of the lithium ion electrolytes such as Li2S·P2S5, Li3YCl6, and Li3InCl6. In some specific implementations, the above solid electrolyte is selected from Li6PS5Cl, Li 10 GeP2S 12 , Li 10 Ge 0.5 Si 0.5 P2S 12 、Li7P3S 11 At least one of the sulfide solid electrolytes such as Li2S·P2S5.
[0055] In some embodiments of the present application, the conductive agent includes but is not limited to one-dimensional conductive agents such as Super P and acetylene black, and one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, etc.
[0056] In some embodiments of the present application, the above-mentioned binder includes but is not limited to one or more of AA, PAA-Li, PAA-Na, PI, CMC, SBR, HNBR, PAN, PVDF, PMMA, and PEO. Preferably, the binder is selected from PAA-Li, PAA-Na, PI, SBR, HNBR, etc.
[0057] In some embodiments of the present application, the solvent used to disperse the mixture includes but is not limited to water, xylene, anisole, tetrahydrofuran, n-heptane, n-hexane, etc.
[0058] In some embodiments of the present application, the aforementioned mixed material is formed on the surface of the current collector to form a negative electrode material layer precursor, and the lithium replenishing surface capacity (i.e., lithium replenishing surface capacity) of the negative electrode material layer precursor is 0.3 mAh / cm 2 -3.0mAh / cm 2 .
[0059] It can be understood that the silicon-based negative electrode material particles include elemental silicon particles, silicon oxide particles, silicon-carbon composite particles, etc. In general, due to the natural oxidation of silicon elements, the surface and / or interior of the above-mentioned silicon-based negative electrode material particles will have a SiO2 layer several nanometers thick. Specifically, in some embodiments of the present application, when the lithium supplement includes any one of Li3P and Li3B, Li3P and Li3B will react with the SiO2 layer of the above-mentioned silicon-based negative electrode material particles to remove lithium and generate lithium-silicon alloys, as well as inorganic phosphides and inorganic borides. These inorganic products will inherit the position of the above-mentioned inorganic lithium supplement and be dispersed in the negative electrode. In this way, the risk of large-area enrichment of lithium-silicon alloys can be significantly reduced, the stability of the prepared negative electrode during storage and subsequent battery assembly can be improved, and the risk of safety accidents can be greatly reduced.
[0060] In some embodiments of the present application, the above-mentioned lithium supplement includes the above-mentioned organic lithium supplement, which can spontaneously undergo a lithium removal reaction, especially under heating conditions. The lithium ions released will quickly diffuse into the interior of the silicon-based negative electrode material particles, react in situ with the silicon atoms inside the silicon-based negative electrode material particles, and generate lithium-silicon alloys; at the same time, the organic lithium supplement after lithium removal is converted into an organic product and dispersed between the gaps of the lithium-silicon alloy (or, between the gaps of the lithium-silicon alloy and the silicon-based negative electrode material particles). In particular, the above-mentioned organic product has a certain viscosity, which can assist in bonding the composite active material particles in the negative electrode to improve the structural stability of the negative electrode, thereby also being beneficial to the cycle performance of the battery; at the same time, the surface of the lithium-silicon alloy particles is a silicon-rich region, which avoids the large-area enrichment of the silicon-lithium alloy in the negative electrode, and improves the stability and safety performance of the negative electrode. It can be understood that if the surface of the silicon-based negative electrode material particles has a SiO2 layer, then the surface of the composite active material particles finally obtained will also have a SiO2 layer accordingly.
[0061] In the present application, it is understandable that in extreme cases, the lithium supplement agent may not react completely. In this case, a very small amount of lithium supplement agent may remain in the final negative electrode, and this very small amount of lithium supplement agent will not affect the performance of the battery.
[0062] An embodiment of the present application provides a negative electrode, including at least one of an inorganic phosphide, an inorganic boride, polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris(4-nitrosophenyl)amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide, and a lithium silicon alloy.
[0063] In some embodiments of the present application, the above-mentioned negative electrode is prepared by the preparation method provided in the examples of the present application.
[0064] As mentioned above, the battery with the above-mentioned negative electrode can achieve a higher first cycle efficiency and a better cycle performance, which will not be repeated here. At the same time, the lithium in the silicon-lithium alloy can also make up for "the continuous loss of active lithium caused by the difficulty of continuous lithium removal in the ordinary silicon-based negative electrode in the relevant technology during the cycle", so the cycle performance of the battery can be further improved. In addition, the above-mentioned polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonic acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexane hexaketone and hexasulfide dipentamethylenethiuram these substances also have a certain viscosity, which can help maintain the structural stability of the negative electrode during the cycle, and is also beneficial to the cycle performance of the battery.
[0065] In the present application, Raman, infrared and other testing methods can be used to characterize the presence of inorganic phosphides, inorganic borides, polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonic acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexanehexaone and hexasulfide dipentamethylenethiuram.
[0066] In some embodiments of the present application, the inorganic phosphide includes but is not limited to phosphorus oxide. The inorganic boride includes but is not limited to boron oxide.
[0067] In some embodiments of the present application, the above-mentioned inorganic phosphide and inorganic boride are in granular form. Specifically, the granular inorganic phosphide and inorganic boride are dispersed in the negative electrode and filled in the gaps between the lithium silicon alloy. In some specific embodiments, the D50 particle size of the above-mentioned inorganic phosphide and inorganic boride is independently 50nm to 800nm. Exemplarily, the D50 particle size of the above-mentioned inorganic phosphide and inorganic boride can be independently 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, etc.
[0068] In some embodiments of the present application, the negative electrode includes at least one of polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexane hexaketone and hexasulfide dipentamethylenethiuram. The above substances have a certain viscosity, which is beneficial to maintain the structural stability of the negative electrode, and thus to the cycle stability of the battery. In some embodiments of the present application, the above substances are distributed between the gaps of the lithium silicon alloy and have a certain bonding effect.
[0069] For the convenience of description, in the following text, inorganic phosphides and inorganic borides are collectively referred to as "first inorganic materials"; polysulfide, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris(4-nitrosophenyl)amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide are collectively referred to as "first organic materials"; and the first inorganic material and the first organic material are collectively referred to as "first material".
[0070] In some embodiments of the present application, the negative electrode includes a current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector. Based on the total mass of the negative electrode material layer, the mass percentage of lithium silicon alloy in the negative electrode material layer is 90% to 99%.
[0071] In some embodiments of the present application, the negative electrode also includes silicon-based negative electrode material particles. At this time, the silicon-based negative electrode material particles are dispersed between the lithium-silicon alloy. As mentioned above, whether there are silicon-based negative electrode material particles in the negative electrode and the mass proportion of silicon-based negative electrode material particles are related to the amount of lithium supplement added during the preparation of the negative electrode, which will not be repeated here. At this time, the sum of the mass proportions of silicon-based negative electrode material particles and lithium-silicon alloy in the negative electrode material layer is 90% to 99%.
[0072] In some embodiments of the present application, the lithium silicon alloy is in granular form, and the D50 particle size of the lithium silicon alloy is less than or equal to 3 μm. For example, the D50 particle size of the lithium silicon alloy may be, but is not limited to, 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, etc. In some specific embodiments, the D50 particle size of the lithium silicon alloy is in the range of 1 μm to 2 μm. For example, the D50 particle size of the lithium silicon alloy may be 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, etc. Controlling the D50 particle size of the lithium silicon alloy within the above range is beneficial to the extraction / insertion of lithium ions and can also make the compaction density of the negative electrode higher, which is beneficial to the energy density of the battery. In the embodiment of the present application, the D50 particle size of the lithium silicon alloy can be measured using a laser particle size analyzer.
[0073] In some embodiments of the present application, when the negative electrode further includes silicon-based negative electrode material particles, the D50 particle size of the silicon-based negative electrode material particles is less than or equal to 3 μm. According to the preparation method of the negative electrode, it is not difficult to understand that the D50 particle size of the silicon-based negative electrode material particles is essentially the same as the D50 particle size of the lithium silicon alloy, so it is not repeated here.
[0074] In some embodiments of the present application, the BET specific surface area of the lithium silicon alloy is 1.0 m 2 / g~2.2m 2 For example, the BET specific surface area of the lithium silicon alloy may be 1.0 m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.15m 2 / g, etc. This is beneficial to the rapid diffusion of lithium ions at the electrode level during the initial lithium insertion of the battery electrode, as well as the deintercalation of active lithium ions during the charge and discharge cycle before complete lithiumization. In the embodiment of the present application, the BET specific surface area of the lithium-silicon alloy is tested by the gas adsorption and desorption method, wherein the gas used can be nitrogen. In some specific embodiments, the BET specific surface area of the silicon-based negative electrode material particles is 1.0 m 2 / g~2.2m 2 / g range.
[0075] In some embodiments of the present application, the lithium silicon alloy and the first material are generated by in-situ reaction with silicon-based negative electrode material particles by at least one of Li3P, Li3B, lithium polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, ketoacid lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cup hexaquinone lithium, tris (4-nitrosophenyl) amine lithium, cyclohexane hexaketone lithium and dipentamethylenethiuram hexasulfide lithium. In this way, the lithium silicon alloy can be evenly dispersed in the negative electrode, greatly reducing the risk of large-area enrichment of the lithium silicon alloy, and greatly improving the safety performance and storage stability of the negative electrode.
[0076] In some embodiments of the present application, the negative electrode further comprises a solid electrolyte. In some specific embodiments, the solid electrolyte in the negative electrode is selected from a sulfide solid electrolyte, wherein the sulfide solid electrolyte includes but is not limited to Li6PS5Cl, Li 10 GeP2S 12 , Li 10 Ge 0.5 Si 0.5 P2S 12 、Li7P3S 11 At least one of Li2S·P2S5, etc. In some specific embodiments of the present application, the solid electrolyte in the negative electrode is dispersed in the negative electrode material layer.
[0077] The present application also provides a secondary battery, including the negative electrode provided in the present application, or including the negative electrode prepared by the method for preparing the negative electrode provided in the present application. Due to the presence of the negative electrode provided in the present application, the secondary battery has a higher first cycle efficiency and better cycle performance.
[0078] In some specific embodiments, when the silicon-based negative electrode material particles are silicon single substance particles, the negative electrode after several charge and discharge cycles includes a negative electrode material layer, the negative electrode material layer includes block amorphous silicon, and the first inorganic material and / or the first organic material is dispersed in the block amorphous silicon.
[0079] In some embodiments of the present application, the secondary battery further includes a positive electrode and a solid electrolyte disposed between the positive electrode and the negative electrode.
[0080] In some embodiments of the present application, the secondary battery is an all-solid-state battery.
[0081] In some embodiments of the present application, the N / P ratio (ratio of the negative electrode capacity to the positive electrode capacity of the battery) of the secondary battery is 1.03-3. For example, the N / P ratio of the secondary battery can be 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.20, 1.50, 2.00, 2.50, 3.00, etc.
[0082] In some embodiments of the present application, the surface capacity of the secondary battery is 4.5-7 mAh / cm 2 , preferably 5 mAh / cm 2 -6mAh / cm 2 In the embodiment of the present application, the surface capacity of the secondary battery is controlled by the load of the positive electrode. A person skilled in the art can select the surface capacity of the battery according to actual needs, and the present application does not set a limit on this.
[0083] In the present application, the above-mentioned positive electrode can be any known positive electrode in the art. The positive electrode includes a positive electrode current collector, a positive electrode active material layer arranged on the surface of the positive electrode current collector, wherein the active material layer includes a positive electrode active material, a solid electrolyte, a binder and a conductive agent. In some embodiments of the present application, the mass ratio of the positive electrode active material, the solid electrolyte, the binder and the conductive agent is 70-85:10-25:0.5-3:0.5-2. Exemplarily, the mass ratio of the positive electrode active material, the solid electrolyte, the binder and the conductive agent can be 70:25:2.5:2.5, 70:25:2:3, 75:23:1:1, 80:18:1:1, 85:13:0.5:1.5, etc. In the present application, the positive electrode current collector can be any known material in the art. In some specific embodiments, the current collector is preferably a carbon-coated aluminum foil. In some embodiments of the present application, the positive electrode active material includes LiNi x Co y Mn z O2, wherein x>0, y>0, z>0, x+y+z=1. In some specific embodiments, the positive electrode active material is in a granular form, and the positive electrode active material particles also have a coating layer, and the coating layer material includes but is not limited to LiNbO3, Li2O·ZrO2, Li3BO3, Al2O3, BaTiO3, Li 1.3 Al 0.3 Ti 1.7 P3O 12, LIPON, TiS2, etc. In some specific embodiments, the thickness of the coating layer is 2nm-15nm, preferably 5nm-10nm. Exemplarily, the thickness of the coating layer can be, but is not limited to, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 12nm, 15nm, etc.
[0084] In some embodiments of the present application, the solid electrolyte in the positive electrode active material layer includes but is not limited to Li6PS5Cl, Li 10 GeP2S 12 , Li 10 Ge 0.5 Si 0.5 P2S 12 、Li7P3S 11 , Li2S·P2S5, Li3YCl6, Li3InCl6 and other lithium ion electrolytes.
[0085] In some embodiments of the present application, the binder in the positive electrode active material layer includes but is not limited to one or more of nitrile rubber (NBR), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), and polytetrafluoroethylene (PTFE). In some embodiments of the present application, the conductive agent in the positive electrode active material layer includes but is not limited to one or more of SuperP, acetylene black, multi-walled carbon nanotubes (MWCNT), vapor-grown carbon fiber (abbreviated as VGCF), graphene, etc.
[0086] In the present application, the solid electrolyte layer is any solid electrolyte layer known in the art. In some embodiments of the present application, the solid electrolyte layer includes a solid electrolyte and a binder. The mass ratio of the solid electrolyte to the binder is 90 to 99.5:0.5 to 10. Exemplarily, the mass ratio of the solid electrolyte to the binder can be 90:10, 92:8, 95:5, 97:3, 99.5:0.5, etc. Exemplarily, the solid electrolyte includes but is not limited to Li6PS5Cl, Li 10 GeP2S 12 , Li 10 Ge 0.5 Si 0.5 P2S 12 、Li7P3S 11, Li2S·P2S5 and other lithium ion electrolytes. Exemplarily, the binder includes, but is not limited to, one or more of PVDF5130, PVDF75130, PVDF21216, PVDF6020, PVDF-HVS900, PVDF-HFP, PVDF-LBG, NBR, HNBR, styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (abbreviated as SBS) or SEBS.
[0087] In some embodiments of the present application, the thickness of the solid electrolyte layer is 20 μm to 50 μm. In some specific embodiments, the thickness of the solid electrolyte layer is 25 μm to 35 μm. Exemplarily, the thickness of the solid electrolyte layer may be, but is not limited to, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0088] In some embodiments of the present application, when assembling a secondary battery, the negative electrode (or, negative electrode precursor), solid electrolyte layer and positive electrode provided in the embodiment of the present application are compositely assembled and then pressure packaged. In some embodiments, after the battery is assembled, it is placed in a warm isostatic press for pressure packaging, and the temperature setting range is 50°C to 160°C. In some specific embodiments, the packaging temperature is 80°C to 140°C. In some embodiments, the packaging pressure is 5MPa to 700MPa. In some specific embodiments, the packaging pressure is 300MPa to 650MPa. In some embodiments, the pressure holding and heat preservation time of the package is 1 to 360min. In some specific embodiments, the heat preservation and pressure preservation time of the package is 10min to 120min. The isostatic pressing is repeated 1 to 10 times, preferably 1 to 3 times. After the battery pressure packaging is completed, the battery is taken out and wiped clean to complete the assembly of the above-mentioned secondary battery.
[0089] The embodiment of the present application also provides an electric device, the electric device comprising the above-mentioned secondary battery. Due to the secondary battery provided by the embodiment of the present application, the electric device has good market competitiveness.
[0090] In some implementations of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic products, vehicles, etc.
[0091] The technical solution of the present application is further illustrated by multiple embodiments below.
[0092] Example 1
[0093] (1) Preparation of negative electrode precursor: Weigh nano-silicon (D50 is 1.0 μm), Li6PS5Cl solid electrolyte, NBR binder and Super P conductive agent in a mass ratio of 70:20:3:7. Fully dissolve NBR in n-heptane solvent. Pre-dry-mix micron silicon, Li6PS5Cl solid electrolyte and Super P conductive agent in a 2000 rpm degassing machine. After mixing evenly, drop an appropriate amount of NBR solution and an appropriate amount of n-heptane solvent, and knead the mixture for 60 minutes. After kneading, add an appropriate amount of n-heptane solvent and triquinoline lithium to the mixture. The amount of triquinoline lithium added corresponds to a lithium supplement amount of 1 mAh / cm 2 , so that the solid content reaches 55%. After 30 minutes of dispersion at 2000rpm, the slurry viscosity reaches 2300Pa / s and then it is coated on the copper-based current collector. After coating, it is dried at 120℃ for 30 minutes. After rolling and compacting the completed electrode sheet, it is baked in a vacuum oven at 150℃ for 12h to obtain the negative electrode precursor.
[0094] (2) Preparation of positive electrode: Weigh the Li3BO3-coated NCM811 positive electrode, Li6PS5Cl solid electrolyte, Super P conductive agent, and PTFE binder in a mass ratio of 85:13:1.5:0.5. The powder was mixed and ground in a high-speed disperser at 2000 rpm for 60 min, and then dry-rolled to form a film and transferred to a carbon-coated aluminum foil by rolling. The surface capacity of the positive electrode was 5 mAh / cm 2 .
[0095] (3) Preparation of solid electrolyte layer: Weigh Li6PS5Cl solid electrolyte and HNBR binder in a mass ratio of 98:2. Dissolve hydrogenated nitrile rubber (HNBR) binder in xylene in advance, then add Li6PS5Cl solid electrolyte and mix by ball milling. The obtained slurry is directly coated on the prepared negative electrode surface and dried at 120°C for 30 minutes under blast conditions. After dyeing, place it at 110°C under vacuum conditions and dry it for 360 minutes to obtain a solid electrolyte layer.
[0096] (4) Battery assembly: The composite electrode sheets of the positive electrode and the solid electrolyte layer-negative electrode precursor prepared above were stacked and welded to the tabs for packaging. The cells were warm isostatically pressed twice at 120°C and 600 MPa for 30 min to obtain the battery of Example 1, which had an N / P ratio of 1.03.
[0097] Example 2
[0098] (1) Preparation of negative electrode precursor: Weigh micron silicon (D50 is 1.6μm), Li6PS5Cl solid electrolyte, PAA (polyacrylic acid) binder and Super P conductive agent in a mass ratio of 95:0:3:2. Fully dissolve PAA in an aqueous solvent. Pre-dry-mix micron silicon, Li6PS5Cl solid electrolyte and Super P conductive agent in a 2000rpm degassing machine. After mixing evenly, drop an appropriate amount of PAA solution and an appropriate amount of aqueous solvent, and knead the mixture for 60 minutes. After kneading, add an appropriate amount of water and naphthalene lithium to the mixture. The amount of naphthalene lithium added corresponds to a lithium supplement amount of 1.2mAh / cm 2 , so that the solid content reaches 50%. After 30 minutes of dispersion at 2000rpm, the slurry viscosity reaches 2100Pa / s and then it is coated on the copper-based current collector. After coating, it is dried at 120℃ for 30 minutes. After rolling and compacting the completed electrode sheet, it is baked in a vacuum oven at 160℃ for 12h to obtain the negative electrode precursor.
[0099] (2) Preparation of positive electrode: Weigh the Li3BO3-coated NCM811 positive electrode, Li6PS5Cl solid electrolyte, Super P conductive agent, and PTFE binder in a mass ratio of 85:13:1.5:0.5. The powder was mixed and ground at 2000 rpm for 60 min in a high-speed disperser, and then dry-rolled to form a film and transferred to a carbon-coated aluminum foil by rolling. The surface capacity of the positive electrode is 6 mAh / cm 2 .
[0100] (3) Preparation of solid electrolyte layer: Li6PS5Cl solid electrolyte and HNBR binder were weighed in a mass ratio of 98:2. The HNBR binder was pre-dissolved in xylene, and then the Li6PS5Cl solid electrolyte was added and mixed by ball milling. The obtained slurry was coated on a polyethylene terephthalate (PET) film and dried at 120°C for 30 minutes under blowing conditions to obtain a solid electrolyte layer.
[0101] (4) The solid electrolyte layer and the negative electrode were laminated and bonded, and warm isostatic pressing was performed twice at 80°C and 500 MPa for 10 min. The solid electrolyte-negative electrode precursor composite electrode was laminated and bonded to the positive electrode, and the tabs were welded and packaged, and warm isostatic pressing was performed once at 120°C and 600 MPa for 30 min to obtain the battery of Example 2, and the N / P ratio of the battery was 1.03.
[0102] Example 3
[0103] The difference from Example 1 is that the added lithium supplement is Li3P.
[0104] Example 4
[0105] The difference from Example 1 is that the added lithium supplement is lithium polysulfide.
[0106] Example 5
[0107] The difference from Example 2 is that the lithium supplement added is Li3B.
[0108] Example 6
[0109] The difference from Example 2 is that the added lithium supplement is lithium crotonate.
[0110] Example 7
[0111] The difference from Example 1 is that the amount of lithium triquinoline added corresponds to a specific capacity of 0.3 mAh / cm 2 Lithium surface capacity.
[0112] Example 8
[0113] The difference from Example 1 is that the amount of lithium triquinoline added corresponds to a specific capacity of 3 mAh / cm 2 Lithium replenishment capacity.
[0114] Example 9
[0115] The difference from Example 5 is that the added lithium supplement Li3B has a specific capacity of 0.3 mAh / cm 2 Lithium replenishment capacity.
[0116] Example 10
[0117] The difference from Example 5 is that the added lithium supplement Li3B has a specific capacity of 3 mAh / cm 2 Lithium surface capacity.
[0118] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0119] Comparative Example 1
[0120] The difference from Example 1 is that no lithium supplement agent is added.
[0121] Comparative Example 2
[0122] The difference from Example 2 is that no lithium supplement agent is added.
[0123] Performance Test:
[0124] (1) First cycle efficiency test: The assembled battery is charged and discharged at a rate of 0.1C to obtain the charge capacity Q charge and discharge capacity Q discharge , the first cycle efficiency is Q discharge / Q charge .
[0125] (2) Cyclic performance test: The batteries of each embodiment and comparative example were charged and discharged 100 times at 25±2° C. and 0.33C rate, and the discharge capacity of the 100th cycle was compared with the discharge capacity of the 1st cycle.
[0126] The test results are shown in Table 1.
[0127] Table 1
[0128]
[0129]
[0130] It can be seen from the data in Table 1 that the secondary battery with the negative electrode according to the embodiment of the present application is a secondary battery with both higher first cycle efficiency and better cycle performance.
[0131] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A negative electrode, characterized in that: It includes at least one of inorganic phosphide, inorganic boride, polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris(4-nitrosophenyl)amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide, and lithium silicon alloy.
2. The negative electrode according to claim 1, characterized in that The lithium-silicon alloy is in granular form, and the D50 particle size of the lithium-silicon alloy is less than or equal to 3 μm; preferably, the D50 particle size of the lithium-silicon alloy is in the range of 1 μm to 2 μm.
3. The negative electrode according to claim 1 or 2, characterized in that The negative electrode further comprises silicon-based negative electrode material particles.
4. The negative electrode according to any one of claims 1 to 3, characterized in that The negative electrode includes at least one of polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris(4-nitrosophenyl)amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide.
5. The negative electrode according to any one of claims 1 to 4, characterized in that The lithium silicon alloy and at least one of the inorganic phosphide, inorganic boride, polysulfide, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride, triquinoline, naphthalene, keto acid, 1,4,5,8-tetrahydroxy-9,10-anthraquinone, [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl acid, selenide triphenylphosphine, cup hexaquinone, tris (4-nitrosophenyl) amine, cyclohexanehexaone and dipentamethylenethiuram hexasulfide are Li3P, Li3 B. At least one of lithium polysulfide ranic acid, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, crotonate lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cuphexaquinone lithium, tris(4-nitrosophenyl)amine lithium, cyclohexanehexaone lithium and dipentamethylenethiuram hexasulfide lithium is reacted in situ with silicon-based negative electrode material particles.
6. The negative electrode according to any one of claims 1 to 5, characterized in that: The negative electrode also includes a solid electrolyte; Preferably, the solid electrolyte comprises a sulfide solid electrolyte.
7. A method for preparing a negative electrode, characterized in that: The following steps are involved: Providing a negative electrode precursor, wherein the negative electrode precursor comprises silicon-based negative electrode material particles and a lithium supplement agent; The lithium supplement agent is de-lithiated, and the de-lithiated lithium ions react with the silicon-based negative electrode material particles to obtain a negative electrode comprising a lithium-silicon alloy; The lithium supplement includes at least one of Li3P, Li3B, lithium polysulfide ranate, 81-33-43,4,9,10-perylenetetracarboxylic acid dianhydride lithium, triquinoline lithium, naphthalene lithium, crotonate lithium, 1,4,5,8-tetrahydroxy-9,10-anthraquinone lithium, lithiated [5,10,15,20-tetraethynylporphyrin] magnesium complex, conjugated sulfonyl lithium, selenide triphenylphosphine lithium, cuphexaquinone lithium, tris(4-nitrosophenyl)amine lithium, cyclohexanehexaone lithium and dipentamethylenethiuram hexasulfide lithium.
8. The preparation method according to claim 7, characterized in that: The lithium replenishing surface capacity of the negative electrode precursor is 0.3 mAh / cm 2 -3.0mAh / cm 2 .
9. The preparation method according to claim 7, characterized in that: The material of the silicon-based negative electrode material particles includes at least one of silicon, silicon oxide and silicon-carbon composite; Preferably, the carbon content of the silicon-carbon composite is less than or equal to 5 wt.%; Preferably, the oxygen content of the silicon oxide is less than or equal to 18 wt.%.
10. The preparation method according to claim 7, characterized in that: The method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain a negative electrode containing a lithium-silicon alloy includes heating the negative electrode precursor; preferably, the heating step includes: drying the negative electrode precursor at 100°C to 150°C for 20min to 40min, and then baking at 100°C to 170°C for 30min to 720min.
11. The preparation method according to claim 7 or 10, characterized in that: The method of removing lithium from the lithium supplement agent and reacting the removed lithium ions with the silicon-based negative electrode material particles to obtain a negative electrode containing a lithium-silicon alloy includes assembling the negative electrode precursor into a battery cell and chemically forming the battery cell.
12. The preparation method according to claim 7, characterized in that: The negative electrode precursor also includes a current collector. The method for providing the negative electrode precursor includes mixing the silicon-based negative electrode material particles and the lithium supplement agent to obtain a mixed material, and placing the mixed material on the surface of the current collector.
13. The preparation method according to claim 12, characterized in that: The mixture includes the silicon-based negative electrode material particles, a solid electrolyte, a conductive agent and a binder in a mass ratio of (60-99): (0-35): (0-5): (1-5).
14. A secondary battery, characterized in that: The secondary battery comprises the negative electrode as claimed in any one of claims 1 to 6, or comprises the negative electrode prepared by the preparation method as claimed in any one of claims 7 to 13.
15. The secondary battery according to claim 14, characterized in that: The secondary battery further includes a positive electrode, and a solid electrolyte disposed between the negative electrode and the positive electrode.
16. An electrical equipment, characterized in that: The electric device comprises the secondary battery according to claim 14 or 15.
Citation Information
Patent Citations
Preparation method for pre-lithiation of silicon monoxide negative pole piece
CN112038583A
Pre-lithiated silicon-based negative electrode plate as well as preparation method and application thereof
CN113363413A
Lithium supplement agent, preparation method thereof and lithium ion battery
CN116207376A
SOLID STATE BATTERY COMPRISING SILICON (Si) AS NEGATIVE ELECTRODE ACTIVE MATERIAL
US20230017977A1